PERTUMBUHAN BENIHIKAN BAUNG (Hemibagrus nemurus) DALAM KERAMBA JARING APUNG YANG DIBERI PAKAN BUATAN DENGAN KADAR PROTEIN BERBEDA [Growth of green catfish (Hemibagrus nemurus) fry in floating net cage feed by artificial food with different protein content] - Ningrum Suhenda; Reza Samsudin; Estu Nugroho (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2010)
The study was conducted to evaluate different protein content of feed on the growth performances of green catfish (Hemibagrus nemurus). Two thousands fingerlings (3.92 ± 0.32 g in averaging of individual body weights) were stocked in each of floating net cage (3x3x3) m3. They were fed daily for four months with diets containing protein content of 27% and 31%. The feed was given in pellet form at 4-8 % of total body weight. Result of this study showed that the fish feed with 31 % protein content gave better growth performances than it with 27 % protein feed. The feed contain of 31% protein was optimum for green catfish fingerlings and gave a higher average individual weight gain (80.48 g), specific growth rate (2.67%), fat retention (29.48%), and better feed conversion ratio (2.28). Survival rates were si-milar for two treatments and ranged between 94.17 to 95.18%.